Artificial Intelligence Services at Academic Libraries in Tanzania: Awareness, Adoption and Prospects - Bakiri, Hussein; Mbembati, Hadija; Tinabo, Rose (University of Dar es Salaam Library Journal, 2024)
Libraries use various information management systems for organizing, packaging, and repackaging services to mention a few. The reliability of these services is highly affected by several factors including; an increase in the number of users, limited resources, decentralized learning, and the emergence of digital resources. Bearing the benefits that AI technologies offer to libraries including cost-effective operations, improved services, and timely analyses, research to investigate the awareness and prospects have been conducted in various countries. Several studies investigated the level of adopting AI technologies for effective services in academic libraries for a particular study area. The general observation from such studies indicates that the level of AI adoption and awareness varies depending on a particular country under investigation. Therefore, due to the diversification of awareness and adoption levels from various areas, it is vital to investigate it in the Tanzanian context. This study aims to investigate the level of awareness and prospects of AI adoption in Tanzanian academic libraries using a qualitative approach in which 36 librarians from 7 giant and widespread higher learning institutions (HLI) are interviewed. The findings reported in this study indicate that the level of awareness is high (68.3%) while that of adoption is low (23%). Furthermore, the findings imply that the demand and readiness for the adoption of AI among librarians is very high. Therefore, this work provides new information to librarians, HLIs ' management, and policymakers regarding the trend of artificial intelligence adoption in academic libraries. The findings reported in this paper can be used by librarians and management to align their plans toward AI adoption for effective and better service delivery.